Fluid‐Assisted Deformation and Strain Localization in the Cooling Mantle Wedge of a Young Subduction Zone (Semail Ophiolite). Issue 9 (21st September 2018) - Prigent, C.; Guillot, S.; Agard, P.; Ildefonse, B.
Abstract: This study reports on feedback mechanisms between fluid migration, ductile deformation, and strain localization processes in an incipiently forming mantle wedge: the basal banded unit of the Semail ophiolite. These peridotites were located right above the plate interface during intraoceanic subduction infancy that ultimately led to ophiolite obduction. During this stage, they were affected by coeval ductile deformation, forming (proto)mylonites at ~900–800 °C to ultramylonites at ~700 °C, and interaction with subduction fluids. From the petrological and microstructural study of these hydrated peridotites and their protolith (preserved lenses of porphyroclastic tectonites), we show that peridotite interaction with hydrous fluids triggered dissolution/precipitation processes. Dissolution of coarser grains and precipitation of new and smaller ones (mainly pyroxenes, spinel, and amphibole) resulted in a drastic grain size reduction, phase mixing and a switch from olivine dislocation to grain size sensitive creep in (proto)mylonites. Data also evidence a feedback process of fluid focusing in actively deforming shear zones. This rapid switch in olivine deformation mechanism, driven by subduction fluid‐peridotite interaction, triggered an intense weakening of the peridotites at ~900–800 °C and a transition from a mechanically decoupled to coupled plate interface (as witnessed by the detachment and underplating of a high‐temperature metamorphic sole to the base of the ophiolite). It also explains the intense strain localization (<1‐km‐thick shear zone) along this ductile portion of the plate interface. Considering that similar mechanisms take place in mature subduction zones, they may explain plate interface coupling at subarc depths in worldwide subduction zones. Key Points: The base of the Semail ophiolite is a proxy for a mantle wedge deforming and interacting with subduction fluids right above a hot plate interface Fluid/peridotite interaction leads to dissolution/precipitation processes, grain size reduction, and peridotite weakening at short time scales Such peridotite weakening explains intense strain localization within the ductile mantle wedge and the observed switch in the subduction interface regime